2013
DOI: 10.1186/1471-2474-14-39
|View full text |Cite
|
Sign up to set email alerts
|

Lung injury-dependent oxidative status and chymotrypsin-like activity of skeletal muscles in hamsters with experimental emphysema

Abstract: BackgroundPeripheral skeletal muscle is altered in patients suffering from emphysema and chronic obstructive pulmonary disease (COPD). Oxidative stress have been demonstrated to participate on skeletal muscle loss of several states, including disuse atrophy, mechanical ventilation, and chronic diseases. No evidences have demonstrated the occurance in a severity manner.MethodsWe evaluated body weight, muscle loss, oxidative stress, and chymotrypsin-like proteolytic activity in the gastrocnemius muscle of emphys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 45 publications
(69 reference statements)
0
26
0
Order By: Relevance
“…Re-establishment of blood flow is essential to salvage ischemic tissues; however reperfusion itself causes further damage to the ischemic tissue, threatening function and viability of the organ. I/R injuries occur in a wide range of organs including the heart, kidney, liver, brain and intestines heart, liver, brain, kidney, colon and skeletal muscles [2-4,31]. Examples of I/R injuries of skeletal muscles in this study can arise as a consequence of a range of vascular events including thrombolytic therapy, organ transplantation, limb trauma, or aortic clamping during repair of abdominal aortic aneurysms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Re-establishment of blood flow is essential to salvage ischemic tissues; however reperfusion itself causes further damage to the ischemic tissue, threatening function and viability of the organ. I/R injuries occur in a wide range of organs including the heart, kidney, liver, brain and intestines heart, liver, brain, kidney, colon and skeletal muscles [2-4,31]. Examples of I/R injuries of skeletal muscles in this study can arise as a consequence of a range of vascular events including thrombolytic therapy, organ transplantation, limb trauma, or aortic clamping during repair of abdominal aortic aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Reperfusion triggers a cascade of acute inflammatory events, leading to cellular death and resulting in tissue dysfunction and necrosis [1]. Most research concerning I/R injury has focused on the heart, kidney, liver, brain, lung and intestines since these tissues are considered vital organs [2-4]. I/R injury to skeletal muscles is also a serious problem however, and can cause local disturbances as well as systemic problems such as crush syndrome due to leakage from muscle cells into circulating blood.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that elevated metabolic rates increase O 2 consumption by the mitochondria in muscle tissues and, consequently, the generation of ROS by mitochondria in the form of superoxide anions. At the same time, adaptive mechanisms appear to decrease oxidative stress by increasing the production and/or mobilization of antioxidants, reducing the production of oxidants, and/or reducing radical leakage during oxidative phosphorylation [38]. Thus, it is reasonable to infer that the differences between the sides of the heart, especially with respect to the increased in the overall height of CL curves obtained in the LH on the 5th day and the decreased CL curve in the RH on the 10th day after tumour implantation, may be due to different responses to different metabolic activities, indicating that the two sides of heart function independently from each other.…”
Section: Discussionmentioning
confidence: 99%
“…), saline (0.3 ml/100 g body weight; control + saline [CS] group); papain (40 mg/100 g body weight in 0.3 ml normal saline) emphysema with papain [EP] group) (Tonon et al . ) or porcine elastase (5.2 IU/100 g body weight [Alfa Aesar, Shrewsbury, MA, USA] in 0.3 mL normal saline) emphysema with porcine elastase [EE] group) (Hayes et al . ) were instilled intratracheally through a 27‐gauge hypodermic needle, according to the procedure described by Mattson et al .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Tonon et al . () demonstrated that muscle atrophy, observed in a model of 60 days of emphysema induced by papain instillation (40 mg/ml) in rats, is mediated by increased muscle proteolysis, with involvement of oxidative stress.…”
mentioning
confidence: 99%